1996
DOI: 10.1242/dev.122.9.2947
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Xcat-2 RNA, a putative germ plasm component, to the mitochondrial cloud in Xenopus stage I oocytes

Abstract: The mitochondrial cloud is a unique cell structure found in stage I Xenopus oocytes that plays a role in mitochondriogenesis and in the distribution of germ plasm to the vegetal pole. Xcat-2 RNA specifically localizes to the mitochondrial cloud and moves with it to the vegetal subcortex in stage II oocytes. Later, in the 4-cell embryo, it is found in a pattern identical to the germ plasm. Following microinjection into stage I oocytes, synthetic Xcat-2 RNAs localize to the mitochondrial cloud within 22 hours. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…We divided The results reveal that nearly all Xenopus germline RNAs are I-S transcripts. These include ddx25 32 , nanos1 33 , and dnd1 34 , and genes recently found to be important for PGC development 35 . Many germline regulators form a protein-protein interaction network (Fig 3C).…”
Section: Soluble-to-insoluble Phase Transition Of Maternal Rna During...mentioning
confidence: 99%
“…We divided The results reveal that nearly all Xenopus germline RNAs are I-S transcripts. These include ddx25 32 , nanos1 33 , and dnd1 34 , and genes recently found to be important for PGC development 35 . Many germline regulators form a protein-protein interaction network (Fig 3C).…”
Section: Soluble-to-insoluble Phase Transition Of Maternal Rna During...mentioning
confidence: 99%
“…Indeed, a similar concept is also seen during Xenopus and Drosophila germ plasm development. Here, different cis-acting elements target mRNAs at different stages of the localization process [126][127][128][129].…”
Section: The Axon-dendrite Paradoxmentioning
confidence: 99%
“…Previous studies have shown the presence of three distinct pathways for vegetal RNA localization. The first one is called the early pathway (also known as METRO) and is used mainly for the localization of germ plasm determinants such as nanos1 ( Forristall et al, 1995 ; Kloc and Etkin, 1995 ; Zhou and King, 1996 ), dazl ( Houston et al, 1998 ) and ddx25 ( MacArthur et al, 2000 ) . During early oogenesis, mRNAs diffuse from the nucleus to be entrapped by the mitochondrial cloud (in fish, called Balbiani body).…”
Section: Introductionmentioning
confidence: 99%